Pengaruh Budaya Terhadap Penerapan Strategi Pemasaran Internasional - Gunawan Aji; Natalia Casha; Siti Fatimah; Allisa Qotrunnada Munawaroh (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to find out how culture influences the implementation of international marketing strategies. The research used in the preparation of this research is qualitative research, namely research procedures that produce descriptive data in the form of written understanding that is observed. Because the research used fully emphasizes library data collection, this type of research is called library research. The results of this study market location is one of the things that traders consider as the cause of market competition and social class, culture and subculture have a significant influence on consumer behavior when making purchases. Culture plays an important role in shaping consumer behavior, for example the way they communicate. Communication has an important role for the success of business competition. Communication is much influenced by cultural factors. So that culture is one of the keys to a company or organization being able to penetrate the international market. Culture has many interconnected components. From these different parts, a deep understanding is needed. These cultural elements influence international marketing, including: Material of Life, Language, social interaction, aesthetics, religion, education, value system.